Filogenia molecular do grupo Piptadenia (Leguminosae, Caesalpinioideae, Clado Mimosoide) e taxonomia do gênero Piptadenia Benth - Ribeiro, Pétala Gomes (2017)
Piptadenia Benth. includes 23 taxa (22 species and one variety) of neotropical distribution, presenting its biodiversity center in the Amazon region. This study includes a phylogenetic approach and a taxonomic review for the species of the genus Piptadenia. The phylogenetic study was performed from the nuclear (ITS and ETS) and plastidial (trnL-F, trnD-T and matK / trnK) sequences analyzed by Maximum Likelihood, Maximum Parsimony and Bayesian Inference criteria. Piptadenia, as hypothesized (and previously shown even with low sampling) is monophyletic with the exclusion of P. viridiflora. The first part of the thesis focused on the inclusion of more samples of P. viridiflora in the matrix used in the previous phylogeny with species of the Piptadenia group with emphasis on Stryphnodendron. We fill in the gaps in the matrix as much as possible and include multiple accesses of P. viridiflora. In all the analyzes, this species appears in an isolated lineage of Piptadenia and sister of the other genera of the group Piptadenia. This result is corroborated with morphological data, including pollen. We describe in chapter 1 the genus Lachesiodendron to accommodate P. viridiflora isolated from the other Piptadenia. The second step was the phylogeny and review of Piptadenia s.s. To accomplish this step, in phylogenetic studies we use the same matrix used for Lachesiodendron and we included all species of Piptadenia except P. imatacae, most represented by multiple accesses. The taxonomic review was performed through the analysis of approximately 10,000 specimens, including types, as well as materials collected and observed during field expeditions. In this study, we propose 13 lectotipifications, 4 new synonyms.